Keragaman Jenis Kapal Perikanan di Kabupaten Takalar - St Nurul Nahdyah; St Aisjah Farhum; Ilham Jaya (Hasanuddin University, 2014)
This research aims to study the variety of fishing boats based on several technical aspects. This research was carried out from September of 2013 through January of 2014. This study collected the sampling data (boats at docking condition) in approximately 10 % of existing population along south coast from Takalar regency. The data were analyzed using cluster and PCA (Principal Componen Analysis) to assess the categorization of the boats based on the main dimension size and the mark of the main dimension ratio. The results showed that there are five groups of categorization which have different characteristics on its group. The group I was the boat which has high width and length (L/B), the group II was the boat which has high height and length ratio (L/D), the group III was the boat which has low height and length percentage (L/D), the group IV the boat which had high length, width, height, and the high water loaded (L, BOA, D, and d), and the group V was the boat which had high width and height ratio (B/D).